PENERAPAN PEMBELAJARAN BERBASIS INKUIRI DALAM PROSES PEMBELAJARAN IPA DI SDN SUSUKAN 08 PAGI - Fadhila Azzahra; Dina Selviana; Firda khoirina; Nisrina Febria Efiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Inquiry-based learning is a method that encourages students to actively participate in the learning process through discovery, investigation, and problem exploration. The purpose of this study is to evaluate how the application of inquiry method in science learning in elementary school. focusing on its impact on critical thinking skills and student engagement. In addition, this learning model also encourages students to actively ask questions and conduct experiments as part of the learning process. The challenge, however, is the need for teachers' skills in managing the classroom and facilitating the inquiry process effectively. The method used was the observation method. This observation involved a number of fourth grade students from SD Susukun 08 Pagi primary school as the sample, which was selected. Data was collected through interviews with the class teacher. Interviews with teachers aimed to gain perspectives on teaching experiences with inquiry methods, including perceived constraints and benefits The observation results show that the use of inquiry-based learning can improve students' active participation and facilitate a deeper understanding of concepts.